ABO alleles are linked with haplotypes of an erythroid cell‐specific regulatory element in intron 1 with a few exceptions attributable to genetic recombination. Issue 1 (14th July 2015) - Nakajima, T.; Sano, R.; Takahashi, Y.; Watanabe, K.; Kubo, R.; Kobayashi, M.; Takahashi, K.; Takeshita, H.; Kominato, Y.
Abstract : Recent investigation of transcriptional regulation of the ABO genes has identified a candidate erythroid cell‐specific regulatory element, named the +5·8‐kb site, in the first intron of ABO . Six haplotypes of the site have been reported previously. The present genetic population study demonstrated that each haplotype was mostly linked with specific ABO alleles with a few exceptions, possibly as a result of hybrid formation between common ABO alleles. Thus, investigation of these haplotypes could provide a clue to further elucidation of ABO alleles.